Introduction to NJWLS 2024-1 - Buch, Anders (Nordic Journal of Working Life Studies, 2024)
Welcome to this first 2024 issue of Nordic Journal of Working Life Studies. The issue includes four research articles from Norway, Sweden, and Denmark.